A 10-year follow-up of the European multicenter trial of interferon β-1b in secondary-progressive multiple sclerosis. (April 2016) - Kuhle, J; Hardmeier, M; Disanto, G; Gugleta, K; Ecsedi, M; Lienert, C; Amato, MP; Baum, K; Buttmann, M; Bayas, A; Brassat, D; Brochet, B; et al.
Objectives: To explore long-term effects of treatment and prognostic relevance of variables assessed at baseline and during the European secondary progressive multiple sclerosis (SPMS) trial of interferon beta 1b (IFNB-1b). Methods: We assessed 362 patients (60% female; median age 41 years; Expanded Disability Status Scale (EDSS): 5.5; 51% randomized to IFNB-1b) for their EDSS and treatment history after 10 years. Non-parametric analysis of covariance (ANCOVA) and multivariate linear regression models were applied. Results: Median EDSS was 6.0 at the end of the randomized controlled trial (RCT), in the IFNB-1b and placebo groups, and 7.0 in long-term follow-up patients (those receiving IFNB-1b in the RCT were 6.5 and those receiving placebo in the RCT were 7.0; p = 0.086). 24 patients (6.6%) were deceased. The EDSS at baseline and the EDSS change during the RCT were the most important predictors of the EDSS 10 years later (partial R 2 : 0.47). The ability to predict changes in EDSS 10 years after the RCT was limited ( R 2 : 0.12). Magnetic resonance imaging (MRI) measures remained in the predictive models, but explained < 5% of the variability. Conclusions: The results from this analysis did not provide convincing evidence to support a favorable long-term outcome in those patients allocated IFNB-1b during the RCT, in our SPMS cohort. The progressive stage of the disease remains largely unpredictable by clinical and conventional MRI measures, so better prognostic markers are needed.